Foreign divestment and insolvency risk: evidence from Nordic MNEs - Iqbal, Arshed; Iqbal, Jamshed; Ojala, Arto (Emerald, 2026)
Purpose This study aims to explore how foreign divestment (FD) affects the insolvency risk of parent firms and examines the moderating role of corporate social responsibility (CSR) in this relationship, an underexplored but critical issue in international business. It focuses on how resource losses from divestment destabilize parent firm solvency, offering insights into the financial vulnerabilities of multinational enterprises (MNEs). Design/methodology/approach Grounded in the resource-based view (RBV) and foreign divestment literature, this study analyzes a longitudinal dataset of 119 publicly listed Nordic MNEs (Finland, Sweden, Norway and Denmark), spanning 667 firm-year observations over 1992–2019. Insolvency risk is measured using Merton’s distance to default (DD) and credit default swap (CDS) spreads, with data from the Credit Research Initiative (CRI), Orbis and Refinitiv Eikon. For the CSR moderation analysis, a sub-sample from 2003 onward is used. Findings Foreign divestment is positively associated with higher insolvency risk, reflecting the financial strain from strategic asset loss or reallocation. Moreover, parent firms with stronger CSR engagement face greater insolvency risk during divestments. Originality/value Integrating RBV and CSR perspectives, this study provides a nuanced view of the financial and strategic consequences of foreign divestment. It offers actionable insights for MNEs managing divestments in volatile markets and underscores CSR’s complex role in mitigating or amplifying financial distress.
Keywords: Foreign divestment; Insolvency risk; RBV; CSR; Firm performance; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|